Pengembangan Bahan Ajar Multilingual Berbasis Konten Dan Konteks Budaya Lokal Etnis Ngada Untuk Siswa Kelas II SD - Gheme, Selviana; Lawe, Yosefina Uge; Noge, Maria Desidaria (Universitas Negeri Makassar, 2022)
The research aimed at: (1) producing content-based multilingual teaching materials and local cultural contexts of ethnic Ngada, (2) knowing the quality of the results of the test results of multilingual teaching material development based on content and local cultural context of ethnic Ngada for grade II elementary school students. The subjects of the trial in this research were SDN Doka class II teacher as a content/material expert, Citra Bakti Junior High School teacher as Indonesian expert, Citra Bakti High School teacher as nn English expert, a bajawa regional language book author as a regional language expert and STKIP lecturer Citra Bakti as a design expert. While the objects studied are the content and context of local Ngada ethnic culture that can be integrated with grade II elementary school material to be used as multilingual teaching material based on content and local cultural context of Ngada ethnicity. This teaching material was developed using the ADDIE model which consists of five steps, namely: (1) analyze, (2) design, (3) development, (4) implementation, and (5) evaluation. Based on the results of the trial, it can be concluded that multilingual teaching materials that have been developed are suitable for use by grade II elementary students.